Evaluation of an Environmentally Sound Port (Ecoport) at the Sibolga Archipelago Fishing Port (PPN Sibolga) North Sumatera Province - Aritonang, Okto Ijen; Zain, Jonny; Yani, Alit Hindri (Jurnal Perikanan dan Kelautan, 2023)
Sibolga Archipelago Fishing Port is one of the fishing ports that carry out export activities with destination countries including Thailand, Vietnam, Peru, and Ecuador. The products caught by the Sibolga Archipelago Fishing Port have not been exported to the European market due to regulations on fishery product export certification. These problems can be overcome by implementing the eco-fishing port concept at the Sibolga Archipelago Fishing Port. The purpose of this study was to evaluate the environmentally sound Sibolga Archipelago Fishing Port (ecoport) according to the ecoport standard formulation. The method used in this study is a survey method. Collecting data using a purposive sampling approach. Data analysis was carried out descriptively using standard eco-fishing port parameters which consisted of four aspects, namely the physical ecology of the port, the socio-economic impacts around the port, handling of caught commodities and monitoring of illegal fishing. The results showed that the physical and ecological aspects got a score of 2.66, the socio-economic impact aspect got a score of 2, the handling of caught commodities got a score of 2 and the illegal fishing aspect got a score of 3. The ecoport index analysis got a score of 2.5 which means that the Sibolga Archipelago Fishing Port has been can be called an ecoport.